One-Month Global Longitudinal Strain Identifies Patients Who Will Develop Pacing-Induced Left Ventricular Dysfunction over Time: The Pacing and Ventricular Dysfunction (PAVD) Study. - Fozia Zahir Ahmed; Manish Motwani; Colin Cunnington; Chun Shing Kwok; Catherine Fullwood; Delvac Oceandy; Alan Fitchet; Grahame Kevin Goode; Matthew Luckie; Amir Masood Zaidi; Rajdeep Khattar; Mamas Andreas Mamas (PLoS ONE)
Background Predicting which individuals will have a decline in left ventricular (LV) function after pacemaker implantation remains an important challenge. We investigated whether LV global longitudinal strain (GLS), measured by 2D speckle tracking strain echocardiography, can identify patients at risk of pacing-induced left ventricular dysfunction (PIVD) or pacing-induced cardiomyopathy (PICMP). Methods Fifty-five patients with atrioventricular block and preserved LV function underwent dual-chamber pacemaker implantation and were followed with serial transthoracic echocardiography for 12 months for the development of PIVD (defined as a reduction in LV ejection fraction (LVEF) ≥5 percentage points at 12 months) or PICMP (reduction in LVEF to <45%). Results At 12 months, 15 (27%) patients developed PIVD; of these, 4 patients developed PICMP. At one month, GLS was significantly lower in the 15 patients who subsequently developed PIVD, compared to those who did not (n = 40) (GLS -12.6 vs. -16.4 respectively; p = 0.022). When patients with PICMP were excluded, one month GLS was significantly reduced compared to baseline whereas LVEF was not. One-month GLS had high predictive accuracy for determining subsequent development of PIVD or PICMP (AUC = 0.80, optimal GLS threshold: <-14.5, sensitivity 82%, specificity 75%); and particularly PICMP (AUC = 0.86, optimal GLS threshold: <-13.5, sensitivity 100%, specificity 71%). Conclusions GLS is a novel predictor of decline in LV systolic function following pacemaker implantation, with the potential to identify patients at risk of PIVD before measurable changes in LVEF are apparent. GLS measured one month after implantation has high predictive accuracy for identifying patients who later develop PIVD or PICMP.